THE CORE TENTS OF THE CONCEPT “FRIENDSHIP” (Konferensiyalar | Conferences, 2024)
The given article is about main components of the concept Friendship in English language. Based on the results of the study of the Roget’s thesaurus, the concept Friendship is interpreted by considering the elements that can be distinguished using themost actively used lexemes:Brotherhood, Likeness, Love, Support.